Trade policy and food security - Martin, Will; Glauber, Joseph W. (CEPR Press, 2020)
The COVID-19 crisis has seen the emergence of export restrictions to ensure food security, although food levels are high and the production outlook for key staples is good. This column reviews the experience of quantitative restrictions during the price spikes of 2007–8 and argues that quantitative restrictions are a source of instability in both the exporting market and the world market. Policymakers should seek to avoid quantitative restrictions to the greatest extent possible.